Pengembangan Lembar Kerja Peserta Didik (LKPD) IPA Berbasis Nilai Karakter - Alwi, Mijhamuddin; Suastra, Wayan; Ariana, Ida Bagus (Universitas Hamzanwadi, 2023)
This study aims at developing teaching materials for Student Worksheets (LKPD) Based on Character Values for fifth graders of SDN 1 Darmasari in the Academic Year 2022/2023. This research is development research with a 4D development model in stages which is simplified into 3 stages, namely, defining, designing, and developing. This research was conducted in the fifth grade of elementary school with 32 students. This development instrument uses validation sheets, and student response questionnaires. The results of the validation of material and language experts with a total score of 58 which are included in the score range of X> 50 in the